Validity in Qualitative Evaluation: Linking Purposes, Paradigms, and Perspectives - Lub, Vasco (International journal of qualitative methods, 2015)
This article provides a discussion on the question of validity in qualitative evaluation. Although validity in qualitative inquiry has been widely reflected upon in the methodological literature (and is still often subject of debate), the link with evaluation research is underexplored. Elaborating on epistemological and theoretical conceptualizations by Guba and Lincoln and Creswell and Miller, the article explores aspects of validity of qualitative research with the explicit objective of connecting them with aspects of evaluation in social policy. It argues that different purposes of qualitative evaluations can be linked with different scientific paradigms and perspectives, thus transcending unproductive paradigmatic divisions as well as providing a flexible yet rigorous validity framework for researchers and reviewers of qualitative evaluations.